Enzymatic esterification of dihydroxystearic acid - Awang, R.; Basri, M.; Ahmad, S.; Salleh, A. B. (Wiley, 2000)
Dihydroxystearic acid (DHSA) ester was synthesized enzymatically to overcome the problems associated with chemical processes. Immobilized enzyme, Lipozyme IM and Novozym 435, were employed as catalysts in the esterification reaction between DHSA and monohydric alcohol. Various factors that may affect the esterification reaction were studied, such as initial water content (aw), organic solvent, substrate concentration and the influence of alcohol chain length. It was found that the percent conversion was higher in organic solvents with log P (the logarithm of the partition coefficient of solvent in octanol/water system) from 2.0 to 4.0. The reaction was not affected by aw from 0.09 to 0.96. Increasing the mole ratio of alcohol to acid above 2.0 did not increase the percent conversion of ester. The ester was identified by Fourier transform infrared and 13C nuclear magnetic resonance spectroscopy.